Implementasi Data Mirroring Pada Metode Hot Standby Redundancy Berbasis Protokol I2C dan Arduino Uno - Arif Nur Agung Laksana; Wijaya Kurniawan; Agung Setia Budi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Each electronic component must have an active time limit and will certainly suffer damage at any time. A system can experience fatal failure if there is damage to components that are crucial. Therefore the crucial component in a system must be fault tolerant, where the system is able to work as it should even though it failed. One way that can be applied to realize a fault tolerant system is by applying the Hardware Redundancy mechanism. Hardware Redundancy is a mechanism to improve system reliability by providing backup components that have the same function as these crucial components. There are several types of this method, one of which is Hot Standby Redundancy in which the method is added a duplicate of the crucial component that is in active condition and will take over the role of the crucial component when the crucial component fails. In this study Hot Standby Redundancy is applied to an Arduino UNO and RFID based door lock system. In that system, which acts as a crucial component is Arduino UNO which acts as a controller in the system. Through I2C serial communication the master sends a probe message periodically to the slave as a sign that the master is still operating or is experiencing damage. The process of switching control of the system is carried out by the slave if the master fails to send the probe message within the specified time period. In addition to redundancy, the system can also synchronize data between the main components and backup components. The process is needed to ensure the two components have similar data. The system test results show that the average time taken by the system to synchronize data with each other is 950.4 microseconds and 784.8 microseconds.